The interplay of DNA binding, ATP hydrolysis and helicase activities of the archaeal MCM helicase. - Liew, L; Bell, S (2011)
The MCM (minichromosome maintenance) proteins of archaea are widely believed to be the replicative DNA helicase of these organisms. Most archaea possess a single MCM orthologue that forms homo-multimeric assemblies with a single hexamer believed to be the active form. In the present study we characterize the roles of highly conserved residues in the ATPase domain of the MCM of the hyperthermophilic archaeon Sulfolobus solfataricus. Our results identify a potential conduit for communicating DNA-binding information to the ATPase active site.